Estimation the best areas of Sun duration hours in Iraq by applying IDW type of interpolation techniques by using GIS program - Al-Hassany, Gheidaa Sabeeh (Iraqi Journal of Science, 2022)
In this paper solar radiation was studied over the Iraqi countary land. The best sun duration hours regions (maximum hours) in Iraq were estimated detected by using Geographic information system (GIS Ver. 9.2) program to apply the (Inverse distance weighting) IDW exact interpolation technique depending on the measured data of metrological stations were distributed on the land areas of Iraq. The total area of the best regions was calculated .Excel 2007 program is used in calculation, graphics and comparison the results.